Analisis Risiko Bencana Kekeringan di Kabupaten Klaten - Prabowo, Kukuh; , Drs. Yuli Priyana, M.Si; , Drs. Munawar Cholil, M.Si (2016)
This drought disaster risk research was conducted in Klaten Regency. The first purpose is to analyze the level of drought hazard, the level of vulnerability against drought and the level of capacity to face drought disaster in Klaten Regency. And the second purpose is to analyze the level of drought disaster risk in Klaten Regency. The method used is secondary data analysis which consist of combined quantitative and qualitative method. The data analysis technique uses quantitative GIS overlay and mathematical computing with classification and scoring of each parameters acording to weighted method to obtain the first research purpose. The second research purpose is obtained using qualitative method trough disaster risk matrix classification by overlaying the first results. The unit of drought risk analysis used here is land units. The results obtained show that the areas in Klaten Regency which have high risk level of drought disaster is covering 4.860,46 hectares (7%) and spread in most of districts in Bayat, Trucuk and Juwiring, and slightly in Gantiwarno and Karangdowo. Areas with moderate risk covering 21.521,02 hectares (31%) is spread in the district of Bayat, Trucuk, Juwiring, Gantiwarno, Karangdowo, Manisrenggo, Ngawen, Tulung, Pedan, Kemalang, Kalikotes, Cawas and Prambanan. While the remaining areas covering 43.641,84 hectares (62%) have low risk level of drought disaster.